Conducted electromagnetic interference mitigation in super-lift Luo-converter for electric vehicle applications - Srinivasan Kalaiarasu; Sudhakar Natarajan (International Journal of Electrical and Computer Engineering (IJECE), 2023)
In this article, a digital chaotic pulse width modulation (DCPWM)-dependent electromagnetic interference (EMI) noise attenuating procedure has been implemented. With the aid of a field programmable gate array (FPGA), a randomized carrier frequency modulation with a fixed duty cycle has been generated through chaotic carrier frequency, and this process is called DCPWM. Conducted EMI suppression is achieved in a 200 kHz, 40 W elementary positive output super lift Luo (EPOSLL) converter using the DCPWM technique. The results are compared and validated with periodic PWM over DCPWM in simulation and hardware with electromagnetic compatibility (EMC) standards. Besides, 9 dBV (2.81 V) of conducted EMI noise has been minimized in the DCPWM approach against periodic pulse width modulation method for the EPOSLL converter in electric vehicles applications.